2023
DOI: 10.1002/mdc3.13690
|View full text |Cite
|
Sign up to set email alerts
|

Expert Consensus on the Use of On‐Demand Treatments for OFF Episodes in Parkinson's Disease: A Modified Delphi Panel

Abstract: BackgroundBackground: On-demand treatments can treat OFF episodes in Parkinson's disease, however, there is limited information regarding when to prescribe them. Objective Objective: Develop expert consensus to determine appropriate clinical factors for considering on-demand treatments. Methods Methods: Using a RAND/UCLA modified Delphi panel method, a panel developed consensus on the use of ondemand treatments for OFF episodes. ResultsResults: The panel agreed on-demand treatments were appropriate when OFF ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
(51 reference statements)
0
4
0
Order By: Relevance
“…The authors of this recommendation concluded that on-demand treatments can help to empower patients to recognise and rapidly treat OFF episodes and should therefore be routinely incorporated into shared clinical decision-making [ 8 ]. More recently, a modified Delphi panel was employed by a group of PD experts to develop consensus on the use of on-demand treatments for OFF episodes [ 19 ]. The experts agreed that on-demand treatment is appropriate for many patients with OFF episodes, including those whose OFF episodes have a significant functional impact on their lives, or follow a pattern of delayed ON, dose failure, or morning OFF; those who use higher doses of levodopa in addition to on-extender treatments; and those who experience treatment-related side effects with levodopa and/or on-extender treatments [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors of this recommendation concluded that on-demand treatments can help to empower patients to recognise and rapidly treat OFF episodes and should therefore be routinely incorporated into shared clinical decision-making [ 8 ]. More recently, a modified Delphi panel was employed by a group of PD experts to develop consensus on the use of on-demand treatments for OFF episodes [ 19 ]. The experts agreed that on-demand treatment is appropriate for many patients with OFF episodes, including those whose OFF episodes have a significant functional impact on their lives, or follow a pattern of delayed ON, dose failure, or morning OFF; those who use higher doses of levodopa in addition to on-extender treatments; and those who experience treatment-related side effects with levodopa and/or on-extender treatments [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, a modified Delphi panel was employed by a group of PD experts to develop consensus on the use of on-demand treatments for OFF episodes [ 19 ]. The experts agreed that on-demand treatment is appropriate for many patients with OFF episodes, including those whose OFF episodes have a significant functional impact on their lives, or follow a pattern of delayed ON, dose failure, or morning OFF; those who use higher doses of levodopa in addition to on-extender treatments; and those who experience treatment-related side effects with levodopa and/or on-extender treatments [ 19 ]. Overall, the experts highlighted that on-demand treatment could be particularly beneficial for individuals whose OFF episodes significantly affect their quality of life [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of ‘on-demand’ rescue therapies are recommended for early-morning akinesia to ensure subjects are able to rapidly achieve an ON state. These include dispersible levodopa formulations, which takes effect more quickly than tablets or capsules, subcutaneous apomorphine pen injection, or orally inhaled levodopa [56] , [57] , [79] .…”
Section: Moving Too Little – Nocturnal Hypokinesias In Pdmentioning
confidence: 99%